Information Technology and Software for Simulation, Synthesis and Research of Data Crypto Protection Methods - Vorobets, Heorhii; Vorobets, Olexandr; Luchyk, Ostap; Rusyn, Volodymyr (Security of Infocommunication Systems and Internet of Things, 2023)
The described information technology for improving data protection (ITIDP) in information communication systems (ICS) is built on the basis of a system approach for the implementation of hardware and software solutions for encryption/decryption of data flows in a given continuum of hardware-software-space-time limitations. The formulation of the task for the implementation of ITIDP is substantiated, and a variant of its architecture is proposed. Examples of the development of possible hardware and software modules and resources for the creation of both ITIDP and ICS with increased protection of real-time data flows are given. The issues of choosing methods and means of data encryption in real technical systems and criteria for assessing the necessity and adequacy of encrypted protection of information flows depending on the usefulness and confidentiality of transmitted data are discussed. As a practical approbation of the application of the proposed technology for solving applied problems, examples of the synthesis and research of a special processor for a block cipher with sequential data processing and dynamic key correction, as well as the results of research and optimization of the RSA encryption model for its use in critical application mobile systems with limited hardware and software resources. It is shown that for systems with limited hardware resources in the RSA model of the cipher, it is more correct to use not the Euler function, but the Carmichael function. This approach, together with the use of a modified method of successive approximations according to the rules of modular algebra for calculating large powers of a large base with the subsequent determination of the remainder by a given modulus of a very large number, makes it possible to remove restrictions on the bit rate of data in low-power computers and speed up data decryption processes. The use of modular architecture in the proposed information technology ensures its scalability and quick reconfiguration for the study of various methods of cryptographic data protection.